Differing Land Use Strategies and Effects in Preexisting Livelihood Systems and Natural Environments of Lower Didessa Valley, Western Ethiopia - Dereje Hinew Dehu; Gemechu Yigezu Ofgeha (Research Synergy Foundation, 2024)
The continuous encroachment of highland cultivators into the lower Didessa River Valley in west Ethiopia since the mid-20th century has brought environmental, economic, and social changes. This study aimed to depict land use changes and their subsequent impacts on preexisting livelihoods and the environment. The travelers’ records, structured interviews with the local communities, and various documents were collected and analyzed qualitatively. The study revealed that the intensified systems of surplus production since 1950 have remarkable and distinct historical political ecology features and impacts by displacing preexisting livelihood systems and reshaping the social and environmental settings in the valley. Thus, (re)considering policies and programs is important to realize sustainable development in the valley. Moreover, further multi-disciplinary research is necessary to understand land use systems and the ecological situations of the Mecha Oromo and Nilotes when planning interventions in the valley.